Constraints Affecting the Adoption of Low-Carbon Agricultural Technologies in Kerala - Anupama, Sudhakaran; K G, Sangeetha; Thomas, Allan (Indian Journal of Extension Education, 2025)
The study was conducted during 2025 in the three districts of Kerala, viz., Thiruvananthapuram, Ernakulam, and Kasaragod, to identify the most critical constraints to farmers' adoption of low-carbon agricultural technologies (LCAT). A descriptive research design was administered for data collection, and 270 farmers were selected using random sampling technique. The Garrett ranking technique was applied to quantify the severity of ten predetermined constraints influencing adoption. The results revealed that unpredictable weather, labour shortage, and high input costs were the most severe constraints limiting adoption. Economic and market-related barriers, including the lack of marketing facilities and inputs, also restricted farmers' willingness to adopt low-carbon agricultural technologies. Knowledge-related constraints, including limited awareness of climate change and low-carbon technologies, were ranked lower, indicating that awareness alone was inadequate to drive adoption without tackling structural and financial barriers. Spearman’s rank correlation revealed the district-wise variation in the severity of constraints, emphasising the need for location-specific extension strategies, within a broader state-level policy framework to promote Kerala’s transition towards carbon-neutral agriculture.